2010
DOI: 10.1039/b926231h
|View full text |Cite
|
Sign up to set email alerts
|

Arylethynyl receptors for neutral molecules and anions: emerging applications in cellular imaging

Abstract: This critical review will focus on the application of shape-persistent receptors for anions that derive their rigidity and optoelectronic properties from the inclusion of arylethynyl linkages. It will highlight a few of the design strategies involved in engineering selective and sensitive fluorescent probes and how arylacetylenes can offer a design pathway to some of the more desirable properties of a selective sensor. Additionally, knowledge gained in the study of these receptors in organic media often leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 123 publications
0
40
0
Order By: Relevance
“…15 Molecular recognition, 6, 7 self-assembly, 8 lock-key modality 9 and reversibility 10 are among the most important features that enable supramolecular chemistry to be employed in many applications including catalysis, 11, 12 delivery, 13, 14 sensing, 1517 and imaging. 18 These applications use building blocks assembled together by intermolecular interactions including electrostatic interactions, 19 hydrogen bonding, 20 π–π interactions, 21 ion-dipole interactions, 22, 23 hydrophobic or solvophobic effects. 24 …”
mentioning
confidence: 99%
“…15 Molecular recognition, 6, 7 self-assembly, 8 lock-key modality 9 and reversibility 10 are among the most important features that enable supramolecular chemistry to be employed in many applications including catalysis, 11, 12 delivery, 13, 14 sensing, 1517 and imaging. 18 These applications use building blocks assembled together by intermolecular interactions including electrostatic interactions, 19 hydrogen bonding, 20 π–π interactions, 21 ion-dipole interactions, 22, 23 hydrophobic or solvophobic effects. 24 …”
mentioning
confidence: 99%
“…The simple derivatization of this class of receptors allows for a “turn-on” fluorescence response to analytes in increasingly polar solvents, a feature often lacking in small molecule organic anion probes. 24 …”
Section: Resultsmentioning
confidence: 99%
“…), 2527 have been exploited for applications such as liquid crystals, 28 lightemitting materials, 29 rotaxane-type structures, 30 molecular magnets, 31 antiangiogenic activity, 32 polymer composites 33 and coordination complexes. 24,34,35 In contrast, the supramolecular chemistry of 2,6-bis(arylethynyl)pyridines has received little attention, perhaps in part due to the scarcity of uniting the fields of molecule/ion recognition with the synthesis of highly-conjugated, carbon-rich materials. Most of the host/guest studies reported have focused on exploiting the pyridine lone pair to bind metal ions 22 or organoiodides.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described a series of both bis(-sulfonamido)- and bis(urea)ethynylpyridines that exhibit positive fluorescent responses to anions with the right combination of electron-donating and/or electron-withdrawing substituents on the pendant phenyl rings. [4, 2529, 77] The bis-ureas (e.g., 25 – 28 , Figure 17) exhibit a rich solvent-based conformational dependence, showing in the solid state that “S”-, “U”- and “W”-type conformations are all possible depending on solvent guests (for instance, “S” shown in 28 , “U” shown in 25 – 27 ). [27] …”
Section: Charged Speciesmentioning
confidence: 99%
“…[3] Alternatively, inclusion of an alkyne linkage between aryl groups has been utilized within synthetic molecular hosts, both for its ability to directly connect two units by an essentially inflexible spacer, and for the electronic conjugation it enables between the two aryl units. [4] …”
Section: Introductionmentioning
confidence: 99%